Identification and Functional Study of Long Non-coding RNA Involved in White Spot Syndrome Virus Infection in White Shrimp, Litopenaeus vannamei - Ifwa Wirasit (Prince of Songkla University, 2024)
Master of Science (Molecular Biotechnology and Bioinformatics(International Program)), 2023